Digital Game-Based Learning: A Comparative Study of DragonBox Algebra and Prodigy in Modern Classrooms - Sisilia Sylviani; Fahmi Candra Permana (Universitas Muhammadiyah Prof. DR. HAMKA, 2026)
Purpose: This study aims to explore the potential and effectiveness of game-based educational applications, specifically DragonBox Algebra and Prodigy, in overcoming students' difficulties in understanding abstract basic algebraic concepts, Design/methodology/approach: This study employs a literature review adapting the Systematic Literature Review (SLR) approach. The sample consists of 20 specific articles selected through purposive sampling from an initial total of 120 articles retrieved from the Scopus and SINTA databases over the last five years. Data were collected using a data extraction instrument validated by mathematics education experts (expert judgment) and analyzed using thematic Content Analysis. Findings: The findings reveal that both applications effectively enhance learning motivation, reinforce conceptual understanding, and support personalized learning. DragonBox's visual and intuitive approach is proven effective in bridging abstract algebra into concrete learning experiences, while the adaptive nature of these applications significantly promotes active student engagement in understanding equation solving. Practical implications: The research findings provide strategic contributions and guidance for teachers and policymakers in developing technology-based learning strategies that are aligned with enhancing digital literacy and meeting the requirements of 21st-century education. Originality/value: The novelty of this study lies in its synergistic comparative approach to two learning applications with distinctly different pedagogical bases—visual-manipulative (DragonBox) and adaptive-immersive (Prodigy)—which have never been analyzed simultaneously in previous literature reviews. Purpose: Penelitian ini bertujuan untuk mengeksplorasi potensi dan efektivitas aplikasi edukatif berbasis permainan, yakni DragonBox Algebra dan Prodigy, dalam mengatasi kesulitan siswa memahami konsep aljabar dasar yang abstrak. Design/methodology/approach: Studi ini menggunakan metode penelitian kajian literatur yang mengadaptasi pendekatan Systematic Literature Review (SLR). Sampel penelitian terdiri dari 20 artikel spesifik yang dipilih menggunakan kriteria purposive sampling dari total awal 120 artikel yang ditemukan pada basis data Scopus dan SINTA dalam rentang publikasi lima tahun terakhir. Pengumpulan data menggunakan instrumen ekstraksi data yang telah divalidasi oleh ahli (expert judgment), sedangkan analisis data menggunakan teknik Content Analysis secara tematik. Findings: Hasil kajian menunjukkan bahwa kedua aplikasi tersebut secara efektif mampu meningkatkan motivasi belajar, memperkuat pemahaman konsep, dan mendukung pembelajaran yang dipersonalisasi. Pendekatan visual dan intuitif DragonBox efektif dalam menjembatani aljabar abstrak menjadi pengalaman belajar yang konkret, sedangkan sifat adaptif aplikasi ini mendorong keterlibatan siswa secara signifikan dalam memahami penyelesaian persamaan. Practical implications: Temuan penelitian ini memberikan kontribusi dan panduan strategis bagi guru dan pembuat kebijakan dalam mengembangkan strategi pembelajaran berbasis teknologi yang selaras dengan peningkatan literasi digital dan pemenuhan kebutuhan pendidikan abad ke-21. Originality/value: Kebaruan (novelty) dari studi ini terletak pada pendekatan komparatif yang sinergis terhadap dua aplikasi dengan basis pedagogis yang saling berbeda, yaitu visual-manipulatif (DragonBox) dan adaptif-immersif (Prodigy), yang belum pernah dianalisis secara bersamaan dalam kajian literatur sebelumnya.